Seroepidemiology and comparative diagnosis of bovine herpesvirus type-1 (bhv-1) in bulls using enzyme-linked immunosorbent assay (elisa), polymerase chain reaction (pcr) and virus isolation (vi) - Oya Bulut; Sibel Yavru (Eurasian Journal of Veterinary Sciences)
In this study, blood, semen and nasal swap samples were taken from 100 clinically healty, indigenous and one year old bulls brought lo Konya Private Konet abbatoir from Konya and its environment with the purpose of slaughter. Semen and nasal swap samples were inoculated into Foetal Bovine Kidney (FBK) and Madin Daiby Bovine Kidney (MDBK) cell cultures. At the end of Incubation, cytopatogenic effect (CPE) was determined in 26 semen and 2 nasal swap samples. Enzyme Linked Immunosorbent Assay (EUSA/Ag) was used for identification of viruses isolated. Two isolates from nasal swap could not be identified, while 15 out of 26 isolates from semen samples was identified as BHV-1 by EUSA Following EUSA/Ag and Polymerase Chain Reaction (PCR) method was applied for detection of BHV-1 in semen and nasal swap samples. One semen sample and 1 nasal swap sample were found as positive by ELISA/Ag. No positive result could be detected in any of nasal swap samples while 23 semen samples were detected as positive by PCR. Besides, Enzyme linked immunosorbent assay (ELISA) and serum micro neutral i zat ion test (serum mNT) were used for detection of antibodies aganist to BHV-1. Twenty-three blood sera samples were detected positive by ELISA, while 14 blood sera samples were detected positive by serum mNT. SNso values of the positive sera samples were detected between 1:1.78-1:22.4.